Faktor-faktor yang mempengaruhi efikasi-kendiri guru sekolah menengah di Malaysia dalam pelaksanaan pendidikan alam sekitar - Mohammad Yusof, Masitah; Muda, Azizi; Abdullah, Ahmad Makmom; Abu Samah, Bahaman; Basri, Ramli; A. Rashid, Noriati (Penerbit Universiti Sains Malaysia, 2013)
The aim of this study was to identify the factors that influence teacher's self-efficacy in Environmental Education in schools. The factors that have been identified are teachers' attitudes and awareness towards the environment and teachers' perception towards school principal's instructional leadership practices. The study involved 300 teachers from 30 secondary schools in Perlis represent North Zone, Selangor represent Central Zone, Pahang represent East Zone, Malacca representing South Zone and Sarawak represents East Malaysia. However, analysis of the study involves 263 respondents (87.7%) from 283 questionnaires collected. Descriptive statistics (mean, standard deviation, frequency and percentage) and inferential statistics (Multiple Linear Regression stepwise method) were used to analyse the data and present the findings. Overall, the results showed that the level of teacher self-efficacy in implementation of Environmental Education is moderate (M = 3.53, SD = .30). According to the perceptions of teachers, principals instructional leadership practices (M = 3:36, SD = .77) was moderate and teacher awareness towards the environment (M = 3.60, SD = .58) was also moderate. However, the attitude towards the environment is good and positive (M = 4.22, SD = .42). The result indicates that the factors that influence teachers self-efficacy in implementation of Environmental Education is the teacher environmental awareness (β = .323, p = .000), teachers' perception towards principals instructional leadership practices for Dimensions of Climate Fostering Teaching and Education Learning Environment (β = .298, p = .001), attitude towards the environment (β = .234, p = .000) and teachers' perception towards principals instructional leadership practices to Dimensions of Teaching and Management Environment Programme (β = –.219, p = .012). These factors explain 34.4% variance of teacher self-efficacy. Based on the findings, some suggestions to the school and the Ministry of Education were presented.